Separate but equal - Stevens, George, 1932-; Poitier, Sidney; Lancaster, Burt, 1913-1994.; Kiley, Richard; Little, Cleavon; New Liberty Productions; Republic Pictures Corporation; Republic Pictures Home Video (Firm); Artisan Home Entertainment (Firm) ([Los Angeles, Calif.] : Republic Pictures Home Video ; [Santa Monica, Calif.] : Distributed by Artisan Home Entertainment, 2003)
This film dramatizes the events leading to the landmark Supreme Court decision outlawing segregation.
Originally broadcast as a motion picture in 1991.
Director of photography, Nic Knowland ; editor, John W. Wheeler ; music, Carl Davis.
Sidney Poitier, Burt Lancaster, Richard Kiley, Cleavon Little.
Rated PG.
DVD.
Closed-captioned.
Keywords: United States. -- Supreme Court -- History -- Drama; Segregation -- Law and legislation -- United States -- Drama; Video recordings for hard of hearing people; Feature films